Why we resist the truth about climate change - Hamilton, Clive (2011)
Climate scientists have unwittingly destabilising the political and social order; the results of their research threaten the future of powerful industrialists and challenge comfortable expectations about unlimited consumption growth. Climate science has discovered that our attempts to subdue and exploit the Earth are now turning back on us and threaten our future in profound ways, just as environmentalists have been arguing for four decades.